DESIGN OF A FUZZY CONTROLLER WITH OUTPUT COMPRESSED, SINGLE-PARAMETER DEPENDENT, S-SHAPED AND Z-SHAPED MEMBERSHIP FUNCTIONS - Gostev, V. I. (Radio Electronics, Computer Science, Control, 2024)
Analytical expressions for controlling impact on a fuzzy controller input are received at outlet separated compressed depending on one parametre figurative and nonfigurative membership functions and questions of designing of an fuzzy controller are stated.